2011
DOI: 10.5539/jas.v3n4p77
|View full text |Cite
|
Sign up to set email alerts
|

Inter Simple Sequence Repeat Fingerprints for Assess Genetic Diversity of Tunisian Garlic Populations

Abstract: Garlic (Allium sativum L.) that is cultivated in Tunisia is heterogeneous and unclassified with no registered local cultivars. At present, the level of genetic diversity in Tunisian garlic is almost unknown. Inter Simple Sequence Repeats (ISSR) genetic markers were therefore used to assess the genetic diversity and its distribution in 31 Tunisian garlic accessions with 4 French classified clones used as control. It was the first time that ISSR markers were used to detect diversity in garlic. Seventeen ISSR pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…ISSR markers can provide a better approximation to true variation among garlic lines. In the same manner, Jabbes et al (2011) reported that, there was sufficient diversity detected using ISSR markers in national collection of garlic germplasm which is crucial for the conservation of genetic diversity and its valorization. In the same context, he indicated that, the availability of a relatively high number of polymorphic ISSR markers reflects the heterozygous genome and that ISSR technique is able to detect as much polymorphism in a vegetative as in sexually propagated species.…”
Section: Issr-pcr and Data Analysismentioning
confidence: 85%
“…ISSR markers can provide a better approximation to true variation among garlic lines. In the same manner, Jabbes et al (2011) reported that, there was sufficient diversity detected using ISSR markers in national collection of garlic germplasm which is crucial for the conservation of genetic diversity and its valorization. In the same context, he indicated that, the availability of a relatively high number of polymorphic ISSR markers reflects the heterozygous genome and that ISSR technique is able to detect as much polymorphism in a vegetative as in sexually propagated species.…”
Section: Issr-pcr and Data Analysismentioning
confidence: 85%
“…Thirty-two onion germplasm resources analysed using ISSR were divided into five groups; the first group Yellow Sweet Spanish system, the second Bejo Daytona cultivar, the third Yellow Globe system, the fourth Yellow Globe Danvers system and the fifth group of Yellow Danvers system (Qijiang & Jia 2007). Jabbes et al (2011) studied diversity in Tunisian garlic genotypes with seven polymorphic ISSR markers. The exotic cultivars Alisa Craig and Brigham Yellow Globe were different compared to the Indian cultivars and Nashik Red and Poona Red were indistinguishable, and similarly N-53 and Bombay Red were quite close (Mahajan et al 2009).…”
Section: Diversity Analysis and Varietal Identification Of Alliumsmentioning
confidence: 99%
“…Due to the limited genome information available for garlic, AFLP, ISSR and SSR markers are most applicable to analysis of garlic diversity. To eliminate some of these complications, isozyme, amplified fragment length polymorphism (AFLP), simple sequence repeat (SSR) and insertion-deletion (InDel) markers have been utilized to reveal genetic diversity in garlic germplasm (Al-Zahim et al 1997, 1999, Ipek et al 2003, Lampasona et al 2003, Jabbes et al 2011, Ovesn a et al 2015, Havey and Ahn 2016, Hirata et al 2016. Recently, SSRs were developed based on transcriptome sequences and successfully used to assess the diversity of garlic germplasm (Ma et al 2009, Zhao et al 2011).…”
mentioning
confidence: 99%